Tasa de Crecimiento, y Composición Química de los Pastos Elefante (Pennisetum purpureum) y Gramalote Morado (Axonopus scopatius) en la Parroquia Guasaganda, del Cantón La Maná. - Arias Hernandez, Benito Rosendo (2022)
Livestock farming currently faces new challenges for animal feeding due to the changing environment that prevents the good growth of pastures. With the objective of evaluating the growth rate and chemical composition of elephant and gramalote grasses in the Guasaganda parish of La Maná canton, an experiment was carried out at the Sacha wiwa experimental center, using six treatments with seven repetitions, under a completely design. random. The treatments were the gramalote and elephant grasses with their different maturity ages 30, 45 and 60 days. The variables to evaluate were; plant height, leaf length, green forage weight, relative growth rate and bromatological composition of the grasses. The means were compared with the Tukey multiple range test at 95% probability. In elephant grass, the highest plant height (152.29 cm), leaf length (77.00 cm) and green forage weight (1652.14 g) were obtained at 60 days of maturity and growth rate relative (4.86 cm/day). Likewise, the best values of dry matter (16.00%) and protein (16.44%) were found on elephant grass. The results showed that elephant grass was found to be better adapted to the subtropical humidity conditions of the Sacha wiwa experimental center, Guasaganda parish, La Maná canton. Because this is the forage grass to achieve the highest growth, as well as the best leaf lengths and green forage production, these being obtained after 60 days of maturity. In addition, elephant grass concentrated the highest production of dry matter and protein at 30 and 60 days of maturity, respectively. This consolidates it as a forage grass with ideal characteristics for animal feeding.